2013
DOI: 10.1093/nar/gkt270
|View full text |Cite
|
Sign up to set email alerts
|

5-Aza-2′-deoxycytidine causes replication lesions that require Fanconi anemia-dependent homologous recombination for repair

Abstract: 5-Aza-2′-deoxycytidine (5-azadC) is a DNA methyltransferase (DNMT) inhibitor increasingly used in treatments of hematological diseases and works by being incorporated into DNA and trapping DNMT. It is unclear what DNA lesions are caused by 5-azadC and if such are substrates for DNA repair. Here, we identify that 5-azadC induces DNA damage as measured by γ-H2AX and 53BP1 foci. Furthermore, 5-azadC induces radial chromosomes and chromatid breaks that depend on active replication, which altogether suggest that tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
80
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 43 publications
13
80
0
Order By: Relevance
“…(B) The sugar in decitabine is natural, enabling DNA incorporation without terminating chain elongation. This shifts the DNA damage curve to the right compared with cytarabine (10,14,33,34), even though the decitabine-DNMT1 DNA-protein cross-link requires repair by homologous recombination (35)(36)(37). The DNA repair delays cell-cycle progression; however, concentrations can be found that deplete DNMT1 without cytotoxicity (green zone), the intent in this clinical trial (unlike with cytarabine, a lower dose need not imply lower efficacy).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…(B) The sugar in decitabine is natural, enabling DNA incorporation without terminating chain elongation. This shifts the DNA damage curve to the right compared with cytarabine (10,14,33,34), even though the decitabine-DNMT1 DNA-protein cross-link requires repair by homologous recombination (35)(36)(37). The DNA repair delays cell-cycle progression; however, concentrations can be found that deplete DNMT1 without cytotoxicity (green zone), the intent in this clinical trial (unlike with cytarabine, a lower dose need not imply lower efficacy).…”
Section: Resultsmentioning
confidence: 96%
“…The pyrimidine ring modification of decitabine subsequently depletes DNMT1 and can also directly hypomethylate DNA, since it cannot accept a methyl group (33,34). High decitabine concentrations, however, do have antimetabolic, DNA-damaging cytotoxic effects (35)(36)(37). Moreover, aggressive DNA-damaging cytotoxic therapy, despite the risk of treatment-related mortality, cures some myeloid cancers (e.g., AML subtypes that do not have p53 system abnormalities); this suggested that cytotoxicity could be the key to durable remissions.…”
Section: Methodsmentioning
confidence: 99%
“…S2) that was shown to activate p53 in HPV þ cells (30). However, DNA damage, induced by increasing concentrations of 5-aza (27), can further contribute to p53 stabilization. We recently reported that HPV is not integrated in a significant portion of HPV þ HNSCC suggesting that HPV episomal maintenance is required in these tumors (8,14).…”
Section: -Azamentioning
confidence: 98%
“…2A). High concentrations of demethylating drugs were shown to induce DNA damage in cells (27). To test whether DNA damage after 5-aza treatment contributed to 5-aza-induced p53 upregulation, we treated UMSCC47 cells with radiomimetic drug zeocin, or 1 or 3 mmol/L of 5-aza-the concentrations that significantly downregulated HPV E6 expression.…”
Section: Hpvmentioning
confidence: 99%
See 1 more Smart Citation